ANALISIS KONTRIBUSI DAN EFEKTIVITAS PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BANJARMASIN DAN KOTA BANJARBARU - Lazwardi, Muhammad Firhan; Oktaviani, Ayu; Kadir (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
Regional original income comes from regional taxes, restaurant tax is classified as a regional tax which plays a large role in contributing to regional original income. This research aims to analyze the effectiveness and determine the tax contribution to restaurants in the city of Banjarmasin and the city of Banjarbaru. The type of data used is quantitative data and the data analysis technique used is descriptive analysis technique